The impact of dysfunctional relationship beliefs on marital satisfaction : comparison of clinical and non-clinical samples : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Dickson, Jan (Massey University, 1996)
Cognitive components of marital distress have been examined in the past decade, but few studies to date have focused on relationship beliefs. The present study is a partial replication of Eidelson and Epstein's (1982) evaluation of the Relationship Belief Inventory, a questionnaire developed by them to assess dysfunctional relationship beliefs. Participants comprised ninety men and ninety-two women (including 90 couples) drawn from both clinical and non-clinical settings. They completed questionnaires which included demographic data, the Relationship Belief Inventory (Eidelson & Epstein, 1982) and the Dyadic Adjustment Scale (Spanier, 1976), a commonly used measure of marital satisfaction. Comparisons were made between responses from clinical and non-clinical groups, between men and women, and between partners. A multiple regression analysis was performed to determine whether specific beliefs represented by the Relationship Belief Inventory were predictive of low levels of marital satisfaction. The results indicated that a belief that disagreement is destructive to a relationship was consistently related to low levels of marital satisfaction. Participants in the clinical group had significantly higher scores on this belief than the non-clinical group, and in the multiple regression equation, this belief was a unique predictor of reduced marital satisfaction. Men were found to hold the belief that sexual perfectionism is important with greater intensity than women. The findings are discussed in terms of their implications for marital therapy.
Keywords: Domestic relations; Psychological aspects; Marital conflict; Marriage